2020
DOI: 10.1016/j.vetmic.2020.108579
|View full text |Cite
|
Sign up to set email alerts
|

A novel low virulent respiratory infectious bronchitis virus originating from the recombination of QX, TW and 4/91 genotype strains in China

Abstract: A B S T R A C TIn China, variants of infectious bronchitis virus (IBV) evolve continually and diverse recombinant strains have been reported. Here, an IBV strain, designated as ck/CH/LJX/2017/07 (referred as JX17) was isolated from chicken vaccinated with H120 and 4/91 in Jiangxi, China, in 2017. Sequence analysis reveals of the S1 gene of JX17 the highest nucleotide identity of 98.15% with that of GI-7 genotype TW2575/98 strain. Furthermore, whole genome analysis among JX17 and other 18 IBV strains demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 37 publications
4
16
0
Order By: Relevance
“…Thus, this is an explanation for why LX4 was the dominant genotype in recent years. Besides, we found that the Taiwan-I-type and New-type isolates showed an increasing trend since 2011 and 2015, respectively, in the country, which agreed with other previous studies ( Xu et al, 2018 ; Fan et al, 2019 ; Huang et al, 2020 ), indicating that the commonly used commercial vaccines could not provide complete protection against these two genotype isolates. The development of new vaccines targeting Taiwan-I-type and New-type isolates should be of practical significance currently.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Thus, this is an explanation for why LX4 was the dominant genotype in recent years. Besides, we found that the Taiwan-I-type and New-type isolates showed an increasing trend since 2011 and 2015, respectively, in the country, which agreed with other previous studies ( Xu et al, 2018 ; Fan et al, 2019 ; Huang et al, 2020 ), indicating that the commonly used commercial vaccines could not provide complete protection against these two genotype isolates. The development of new vaccines targeting Taiwan-I-type and New-type isolates should be of practical significance currently.…”
Section: Discussionsupporting
confidence: 90%
“…These 212 IBV isolates were isolated in 22 provinces or autonomous cities (zones) with a wide geographical range in China ( Supplementary Figure 1 ). The available complete sequences of 33 reference IBV strains ( Supplementary Table 3 ) included the commonly used live vaccine strains in China, and the dominant genotypes and serotypes around the world ( Thor et al, 2011 ; Mo et al, 2013 ; Zhao et al, 2016 , 2017 ; Fan et al, 2019 ; Huang et al, 2020 ). Among all complete genome sequences of IBV isolates from other countries retrieved from the GenBank database, 68 IBV isolates with known sampling dates and geographic locations were chosen for analysis together ( Supplementary Tables 4 , 5 ).…”
Section: Methodsmentioning
confidence: 99%
“…In the animal pathogenicity test, chickens infected with the GX-NN160421 showed mild respiratory symptoms with 76.67% morbidity and 3.33% (1/30) mortality, which contrasts with the 90% morbidity and 50% mortality in the field case. A similar case has been previously reported [ 17 ]. The possible reason might be that the IBV strain GX-NN160421 was not the only causative pathogen for the clinical outbreak.…”
Section: Discussionsupporting
confidence: 85%
“…In addition to S protein, coding regions of ORF1ab, especially those of NSP2, NSP3 and NSP16, also harbor many hotspots for mutation and recombination (Thor et al 2011 ). Similar to mutations, most recombination events of IBV genome also tend to reduce the virulence of IBV (Huang et al 2020b ).…”
Section: The Taxonomy Host Range and Pathogenicity Of Cornidovirineaementioning
confidence: 99%